Capital Markets and SMEs in Emerging Markets and Developing Economies : Can They Go the Distance? - World Bank Group (World Bank, Washington, DC, 2020)
Small and medium enterprises (SMEs) face significant financing gaps that stifle innovation and economic growth. The credit gap alone is estimated at dollar 4.5 trillion as of 2017 for emerging markets and developing economies (EMDEs) only. Bank financing has been the traditional source of external financing to SMEs; however, since the global financial crisis that started in 2007, there has been an active debate about the role that capital markets can play in SME financing. This report seeks to enhance practitioners’ understanding of the potential role that capital markets can have in SME financing in EMDEs. the report reviews global experiences in the use of capital markets solutions and, more generally, in market-based solutions to expand SME financing with a view to identifying key preconditions and challenges for EMDEs implementing the solutions. The report looks at both indirect and direct mechanisms for SME financing, such as capital markets solutions, lending conditions, instruments such as SME loan securitization and others, as well as both debt and equity financing solutions.